Chest tube simulation: experience report and brief review (Research, Society and Development, 2022)
Chest tube insertion is one of the most performed surgical procedures in medical practice, being performed in Brazil by both general practitioners and experienced surgeons. This study aimed to report an experience with the application of an animal model to simulate chest drainage, as well as review the scientific literature available on the subject. In our experience, pork rib pieces were used to simulate the human rib cage, where medical students trained the procedure with the help of a thoracic surgeon. The porcine model used proved to be satisfactory, allowing the study of anatomical correlations and surgical technique among the students. In our review, we found 5 other experiences reported, 3 in a synthetic anatomical model, 1 in a porcine model and 1 comparative study between a synthetic model and a cadaver model. All models proved to be efficient for training students, but they present differences in terms of cost and durability, with the synthetic model being the most cost-effective alternative.